Adeno‐Associated Virus Production, Purification, and Titering. Issue 4 (29th November 2018) - Chen, Yong Hong; Keiser, Megan S.; Davidson, Beverly L.
Abstract: Adeno‐associated virus (AAV) vectors are exemplary tools for studying gene function in vivo and are particularly favorable for transferring genes of interest into brain tissues. They have shown great promise as a gene therapy vector for preclinical and clinical applications. However, the ability to use this tool is often hampered because the viruses themselves are not readily available. Many methods have been developed for AAV production. Here, we describe a simple method for small‐ to medium‐scale (10 12 ‐10 13 viral particles) production of AAV based on Polyethylenimine Max (PEI Max)–mediated triple transfection of HEK 293 cells and purification with iodixanol gradient ultracentrifugation. These methods will provide users with ample material of sufficient quality for performing in vivo gene transfer. © 2018 by John Wiley & Sons, Inc.